Answer:
f(- 6) = 9
Step-by-step explanation:
to evaluate f(- 6), substitute x = - 6 into f(x)
f(- 6) = - × - 6 + 5
= - + 5 = 4 + 5 = 9
Answer:
A
Step-by-step explanation:
The quotient is x^2
The remainder is 2
Step-by-step explanation:
We need to divide:
The division is shown in figure attached.
The quotient is x^2
The remainder is 2
Keywords: Division of polynomials
Learn more about Division of polynomials at:
#learnwithBrainly
Answer:
1.
Step-by-step explanation:
1. sin 241 = sin(61 + π) = -sin61 = -t^(1/2)
2. sin^2 + cos^2 =1, cos 61= (1-t)^(1/2)
3. [2sin^2 (x)sin(x) +2cos^2 (x)sin(x)]/2cos(x) = 2sin(x) / 2cos(x) = tan(x)
4. tan (x), x do not equal to (π/2 +or- kπ)
x do not equal to 90,270。